Self-catalytic VLS growth one dimensional layered GaSe nanobelts for high performance photodetectors. (July 2018) - Tang, Luping; Zhao, Zixiang; Yuan, Shuangping; Yang, Tiefeng; Zhou, Bingxin; Zhou, Hong
Abstract: Layered GaSe is an important binary semiconductor because of its anisotropic crystallography characteristics, wide band gap and attractive optical and electrical properties. Here, we report the self-catalytic growth of GaSe nanobelts via a simple chemical vapor deposition method. The quality of the as-grown nanobelts have been confirmed by transmission electron microscope and photoluminescence spectra. The field-effect transistors based on these individual GaSe nanobelts have been fabricated and show p-type semiconducting behaviors and on-off ratio of 10 6 . The GaSe nanobelts not only show good responsivity of 164.4 A W −1, but also exhibit excellent stability and reliability, which are superior to their bulk counterparts. These results make GaSe nanobelt a promising optoelectronic material in integrated electronic/optoelectronic devices. Highlights: Single crystal GaSe nanobelts were obtained via a chemical vapor deposition method. Our devices showed p-type behavior with high room-temperature on/off current ratio of ∼10 6 . High responsivity of 164.4 A W −1 was achieved in the individual GaSe nanobelt photodetector.